Teaching students the technique of upper ball transfer in volleyball with the use of sports and technical devices - Afzalova, A.N.; Antonova, T.V.; Shuvalova, N.V. (Theory and Practice of Physical Culture, 2025)
Purpose of the study. Theoretically substantiate and develop the content of teaching 10-11-year-old schoolchildren the technique of upper ball transfer in volleyball using sports and technical devices. Methodology and organization of research. The pedagogical research was conducted on the basis of I. P. Tchaikovsky MBOU Secondary School No. 1, Votkinsk. The experiment involved 15 schoolchildren (10-11 years old), of which two groups were formed: students of group 1 (n=8) – the control group (CG) and students of group 2 (n=7) – the experimental group (EG). The control group of students was engaged in the traditional method of technical training of school students in the "Volleyball" section, and the students of the experimental group used sports and technical devices. Research results and conclusions. The content of teaching 10-11-year-olds the technique of upper ball passing in extracurricular volleyball classes developed by us consisted of two stages of training:" initial stage "and" advanced stage". At the "initial stage" we use sports and technical devices to more accurately set up the transmission technique, at the second stage we carry out the learning process through exercises in pairs and outdoor games. We also developed a set of exercises with the use of sports and technical devices, including such devices as a hoop on a grid, suspended and movable hanging rings, "Gander".